The Effect of Workload and Stress on Work Productivity in Nurses at Sabah Al Ahmad Urology Center Kuwait - Mochamad Robby Fajar Cahya; Nafiah Ariyani; Kholil (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Nursing is a profession that receives a lot of pressure and has an extreme workload that can cause stress and reduce work productivity due to the heavy tasks that nurses have to perform, which in turn can result in considerable work-related tension. This is especially relevant during the current period of uncertainty that has emerged as a result of the COVID-19 pandemic Objective : Toevaluate the effect of workload and stress on the work productivity of nurses. In a complex healthcare environment, nurses often face high workload demands and significant stress levels, which can affect their productivity. Methods: This research method uses a quantitative approach with a Cross Sectional research design. Data was collected through a questionnaire given to a sample of nurses working in hospitals. This questionnaire includes a measurement scale to measure the nurse's workload level, stress level, and work productivity level. Data analysis was carried out using SEM PLS. Results: The results of the analysis showed that there was no significant relationship between workload and nurse work productivity (p value 0.194 >0.05) and there was a significant relationship between work stress and nurse work productivity (p value 0.0000 <0.05). The higher the level of workload experienced by nurses, the higher the level of stress they experience, and the lower their work productivity. The implication of this study is the importance of effective workload management and stress management in an effort to increase the work productivity of nurses. Conclusion: There is a significant relationship between work stress and nurse work productivity in SAUC. This means that the work stress felt by nurses at SAUC affects the work productivity of nurses at SAUC, when the level of stress experienced by nurses at SAUC is getting higher, it will cause a decrease in the work productivity of nurses at SAUC.